2014
DOI: 10.1890/13-1455.1
|View full text |Cite
|
Sign up to set email alerts
|

An exotic herbivorous insect drives the evolution of resistance in the exotic perennial herb Solidago altissima

Abstract: Invasive plants often experience rapid changes in biological interactions by escaping from their original herbivores at their new habitats, and sometimes re‐associating with those herbivores afterwards. However, little is known about whether the temporal changes in herbivorous impact work as a selective agent for defensive traits of invaded plants. Solidago altissima (goldenrod) is a North American perennial that has widely invaded abandoned fields in Japan. Recently, an herbivorous insect Corythucha marmorata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 63 publications
2
55
0
Order By: Relevance
“…Consistent with our prediction, infested populations showed higher resistance to the specialist O. communa and lower resistance to the generalists H. armigera and S. litura . While several studies have shown increased resistance to introduced specialist herbivores after re‐exposure to them (Fukano & Yahara, ; Sakata et al, ), our experiment provides the first evidence that such a reassociation can cause a decline in resistance to generalist herbivores. The observed results support the SDH from a new viewpoint.…”
Section: Discussionmentioning
confidence: 47%
“…Consistent with our prediction, infested populations showed higher resistance to the specialist O. communa and lower resistance to the generalists H. armigera and S. litura . While several studies have shown increased resistance to introduced specialist herbivores after re‐exposure to them (Fukano & Yahara, ; Sakata et al, ), our experiment provides the first evidence that such a reassociation can cause a decline in resistance to generalist herbivores. The observed results support the SDH from a new viewpoint.…”
Section: Discussionmentioning
confidence: 47%
“…We measured lace bug population growth and damage level in the fourth week as indices of resistance of S. altissima because the fourth week is an appropriate time for measuring the population growth of lace bugs (Sakata et al. ). Both indices were used to complementarily evaluate plant resistance.…”
Section: Methodsmentioning
confidence: 99%
“…For an index of sexual reproduction, the number of flowers was calculated by the following equation obtained from Sakata et al. (): number of flowers = e 0.11 H + 0.05 W + 3.15 , where H and W are height and width of the capitulescence, respectively. All plants were harvested on 30 November 2013, and the total number of rhizomes was counted and their length was measured.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations